Chimeric RNA ASTN2-PAPPAas aggravates tumor progression and metastasis in human esophageal cancer. (31st March 2021) - Wang, Lu; Xiong, Xiao; Yao, Zhimeng; Zhu, Jianlin; Lin, Yusheng; Lin, Wan; Li, Kai; Xu, Xiaozheng; Guo, Yi; Chen, Yuping; Pan, Yunlong; Zhou, Fuyou; et al.
Abstract: Transcription-induced chimeric RNAs are an emerging area of research into molecular signatures for disease biomarker and therapeutic target development. Despite their importance, little is known for chimeric RNAs-relevant roles and the underlying mechanisms for cancer pathogenesis and progression. Here we describe a unique ASTN2-PAPPAantisense chimeric RNA (A-Pas chiRNA) that could be the first reported chimeric RNA derived from the splicing of exons and intron antisense of two neighboring genes, respectively. Aberrant A-Pas chiRNA level in ESCC tissues was associated with tumor progression and patients' outcome. In vitro and in vivo studies demonstrated that A-Pas chiRNA aggravated ESCC metastasis and enhanced stemness through modulating OCT4. Mechanistic studies demonstrated that ERK5-mediated non-canonical PAF1 activity was required for A-Pas chiRNA-induced cancer malignancy. The study defined an undocumented function of chimeric RNAs in aggravating cancer stemness and metastasis. Highlights: The currently reported A-Pas chiRNA could be the first chimeric RNA derived from the splicing of exons and intron antisense of two neighboring genes, respectively. Aberrant A-Pas chiRNA level in ESCC tissues is significantly associated with disease progression and patients' prognosis. A-Pas chiRNA promotes ESCC cells metastasis and enhances stemness through modulating OCT4. ERK5-mediated non-canonical PAF1 activity is required for A-Pas chiRNA-induced cancer malignancy.